ALTERNATIF MEDIA PENYIMPANAN HASIL EVALUASI PEMBELAJARAN BERBASIS SMARTPHONE MENGGUNAKAN APLIKASI ABSENSI SISWA - Savira, Liza; Julrissani, Julrissani (STKIP Persada Khatulistiwa Sintang, 2026)
This study aimed to examine the use of a smartphone-based Student Attendance application as an alternative medium for storing learning evaluation data, including attendance and students’ scores, while integrating digital literacy into evaluation activities at SD Negeri 2 Syamtalira Bayu. The research employed a qualitative method with a descriptive case study approach. The subjects consisted of four teachers (two classroom teachers and two subject teachers) selected through purposive sampling. Data were collected through observation, interviews, and documentation to explore experiences and benefits of using the application. Data analysis was conducted through data reduction, data display, and conclusion drawing, supported by validity checks to ensure the credibility of findings. The results indicated that the application effectively improved the efficiency and accuracy of managing evaluation data. It met key criteria such as security, accessibility, accountability, practicality, and cost-effectiveness. Features such as automatic data backup and score annotation enhanced reliability and transparency. Furthermore, its implementation supported the development of digital literacy within the school environment. In conclusion, the smartphone-based Student Attendance application is an innovative and feasible solution for storing learning evaluation data in elementary schools.